The Effectiveness Of Group Guidance Using Role-Playing Techniques Based On Cognitive Reframing In Improving Students Emotional Regulation - Mutiara Fadilah; Mahdum; Munawir (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
pretest-posttest experimental design was employed. The participants consisted of 15 students selected through purposive sampling based on low and moderate levels of emotional regulation. Data were collected using an emotional regulation scale consisting of 26 valid items measured on a Likert scale. Data analysis was conducted using descriptive statistics, the Wilcoxon Signed-Rank Test, and normalized N-Gain analysis.The findings revealed that before the intervention, 20% of students were in the low category and 80% were in the moderate category. After eight sessions of group guidance services, no students remained in the low category, 46.6% were in the moderate category, and 53.3% reached the high category. The Wilcoxon Signed-Rank Test indicated a significant difference between pretest and posttest scores, with a significance value of p = 0.001. Furthermore, the mean N-Gain score was 0.45, indicating a moderate level of effectiveness. Improvements were observed across all aspects of emotional regulation, including emotional acceptance, emotion regulation strategies, goal-directed behavior, and control of emotional responses.These findings suggest that group guidance services using role playing techniques based on cognitive reframing are effective in improving students' emotional regulation. Through role playing activities and cognitive restructuring processes, students become more capable of recognizing, accepting, managing, and expressing their emotions appropriately in various situations. Therefore, this intervention can be considered a practical counseling strategy for enhancing students' emotional regulation in school settings.